Maximum Power Point Tracking System for Wind Generator Using MATLAB. (International Journal of Engineering and Computer Science, 2015)
:The purpose of this work is to develop a maximum power tracking control strategy forvariablespeed wind turbine systems. Modern windturbine control systems are slow, and they depend on the designparameters of the turbine and use wind and / or rotor speed measurements as control variable inputs. Thedependence on the accuracy of the measurement devices makes the controller less reliable. The proposedcontrol scheme is based on the stiff system concept and provides a fastresponse and a dynamic solution tothe complicated aero dynamic system. This control scheme provides a response to the wind changes without the knowledge of wind speed and turbine parameters.The system consists of a permanent magnetsynchronous machine (PMSM), a passive rectifier, adc/dcboostconverter, acurrent controlled voltages our ceinverter, and a micro controller that commands thedc/dcconverter to control the generator for maximum power extraction. The microcontroller will also be ableto control the current output of the three-phaseinverter. In this work, the aerodynamic characteristics ofwind turbines and the power conversion system topology are explained. The maximum power trackingcontrol algorithm with avariable stepestimat or is introduced and the modeling and simulation of the windturbine generator system using the MATLAB/SIMULINK® software is presented and its results show, atleast in principle, that the maximum power tracking algorithm developed is suitable for wind turbinegeneration systems.